ANALISIS HUBUNGAN KEMAMPUAN BERFIKIR KREATIF DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMPN 14 BANDAR LAMPUNG - Sellvi Wulandary; Indaryanti Indaryanti; Jeri Araiku; Scristia Scristia (Lentera Sriwijaya : Jurnal Ilmiah Pendidikan Matematika, 2021)
research is a type of quantitative research with a correlation reserch method. This study aims to determinane wheather there is a positive and significant relationship between creative thinking skills and stident’s problem solving abilities. The sample used in this study were students of class VIII.A SMPN Bandar Lampung with 32 students. The data collection technique used in this study consisted of 3 stages, namely preparation, implementation and the final stage. The Instrument used in this study is a written test. The data analysis technique is correlation analysis which consists of prerequisite test analysis and hypothesis testing. Based on the research results, it shows that tcount(3.882)> ttable(2.042) and the sig value (0.001)< (0.05) with a correlation value of 0.578. So it can be concluded that the relationship between creative thinking skills and students problem solvig abilities is positive and significant, with a fairly close relationship. The contribution of creative thinking skills to problem solving abilities is 33.4%.